What are an Effective and Efficient Organizational Structure and Job Description for Traditional Markets? Phenomenologica Studies - Alfira Sofia; Budi S Purnomo; R Nelly Nur Apandi (The International Journal of Business Review (The Jobs Review), 2022)
Abstract. The success of the market will be supported by human resources who manage the market. The limited budget causes the need for an appropriate organizational structure and job description. Respondents in this study are traditional market managers and experts in market governance. The study results provide an overview of the ideal organizational structure in market management, divided into three major parts: the revenue administration section, the cost administration section, and the security and cleanliness section. This study provides implications for traditional market managers in applying the organizational structure and job descriptions generated.Keyword. organizational structure; job description and traditional markets